Evaluating climate hazard hotspots and hazard impacts in Sri Lanka: an analysis of historically reported data - Alahacoon, Niranga; Thathsarani, Geethya; Sivananthan, Piriyanka; Amarnath, Giriraj (International Water Management Institute (IWMI), 2024)
This assessment explores the impact of various natural disasters in Sri Lanka, including floods, landslides, cyclones, droughts, lightning, heavy rainfall, and strong winds. Utilizing historical data from the Disinventar database, the analysis focuses on mapping the occurrences and impacts of significant hazards such as floods, droughts, strong winds, landslides, lightning, cyclones, and heavy rain from 1974 to 2022. Notably, landslides, droughts, and floods dominate the landscape of hazards in the country. During 1974 to 2022 period, a total of 182 cyclones, 2,370 droughts, 7,829 floods, 2,633 incidents of heavy rain, 2,109 landslides, 1,243 lightning events, and 8,754 occurrences of strong winds were documented. Among these, strong winds emerged as the most prevalent hazard, accounting for approximately 35% of total incidents, followed by floods at 21%. Lightning events represented 13% of occurrences, indicating a relatively frequent presence. The analysis reveals that the Ratnapura district is significantly affected by a combination of hazards, with frequent incidents of floods, strong winds, landslides, and lightning events. In terms of human impact, landslides recorded the highest number of deaths, while cyclones resulted in the most injuries, particularly noted in Ampara district, which reported 417 injury cases. Drought is highlighted as the most impactful disaster overall, affecting 4,366,458 individuals during the study period, while Kurunegala district suffering the most substantial crop damage, impacting an area of 44,383.41 hectares (86%) during drought. Flooding also significantly affected Badulla, where it impacted 8,909.162 hectares (14%). This study underscores the urgent need for effective disaster management strategies to address the challenges posed by these recurrent hazards in Sri Lanka.